The Influence of Age on the Death Rate of Hajj Pilgrims in South Sumatra in 2024 - Asrita Fajriani (Al Makki Health Informatics Journal, 2024)
The Hajj pilgrimage is a significant religious obligation for Muslims, but it presents various health risks, particularly for older pilgrims. This study aims to identify the influence of age on the number of Hajj pilgrims from South Sumatra in 2024. A quantitative research approach was employed, collecting and analyzing mortality data for pilgrims based on age groups. Primary data were gathered from a survey conducted among health congregants before departure, while secondary data were sourced from official reports from the Ministry of Religion and Health Services. The analysis revealed that age significantly influences the number of deceased pilgrims, particularly among those aged over 60. This age group faces a higher risk of mortality due to vulnerable health conditions and the prevalence of chronic diseases such as heart disease, diabetes, and hypertension, which are exacerbated by the physical demands of the Hajj pilgrimage. The findings emphasize the need for careful attention and preparation regarding the health of older congregants. Intensive monitoring is essential to ensure that this group can undertake the Hajj pilgrimage safely and optimally. It is recommended to develop specialized health programs for elderly Hajj pilgrims to mitigate the risk of mortality during their religious observance. These programs should focus on health assessments, education on managing chronic conditions, and strategies for coping with the physical demands of the pilgrimage.